The evolving transmission of uncertainty shocks in the United Kingdom - Haroon Mumtaz (Econometrics, 2016)
This paper investigates if the impact of uncertainty shocks on the U.K. economy has changed over time. To this end, we propose an extended time-varying VAR model that simultaneously allows the estimation of a measure of uncertainty and its time-varying impact on key macroeconomic and financial variables. We find that the impact of uncertainty shocks on these variables has declined over time. The timing of the change coincides with the introduction of inflation targeting in the U.K.
Keywords: C15; C32; E32; 330; TVP-VAR; stochastic volatility; uncertainty shocks